PENGARUH EARNING PER SHARE, RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Furniawan Furniawan (The Asia Pacific Journal Of Management Studies, 2021)
One of the factors to consider in investing in the capital market is the stock price. Stock price is one indicator of company management in determining the value of the company. results in increasing profits will provide satisfaction to investors. The stock price that continues to increase illustrates the good value of the company so that it will make it easier for management to get capital or funds from outside parties. quantitative descriptive research method. The type of data in this study is secondary data found on the official website of the Indonesia Stock Exchange, namely www.idx.co.id in the form of financial statement data on LQ45 companies listed on the Indonesia Stock Exchange. Partially, Earning Per Share has a significant influence on stock prices. Partially Return on Equity does not have a significant effect on stock prices. Partially Net Profit Margin has a significant negative effect on stock prices. Together, the variables of Earning Per Share, Return on Equity and Net Profit Margin have a significant effect on stock prices.